Clinical and Patient-reported Outcomes After Posterior Versus Transforaminal Lumbar Interbody Fusion—A Propensity Score-matched Cohort Study on 422 Patients with 2-year Follow-up. Issue 2 (15th January 2022) - Ohrt-Nissen, Søren; Carreon, Leah Y.; Andresen, Andreas K.; Andersen, Mikkel Ø.; Udby, Peter
Abstract : Study Design: This was a dual-center study over an eight-year period on patients undergoing single level fusion surgery with either posterior- (PLIF) or transforaminal lumbar interbody fusion (TLIF). We analyzed prospectively collected pre- and postoperative data from the national Danish surgical spine database (DaneSpine). Objective: The aim of this study was to compare clinical and patient-reported outcome (PRO) 2 years after TLIF or PLIF in patients with symptomatic lumbar mechanical disc degeneration. Summary of Background Data: PLIF and TLIF are well-described techniques for treating lumbar mechanical disc degeneration but whether the theoretical differences between the two techniques translate to different clinical outcomes is unknown. Methods: The primary outcome was Oswestry Disability Index (ODI) score at 2-year follow-up. Secondary outcome measures were scores on the European Quality of Life–5 Dimensions (EQ-5D) and visual analog scale (VAS) and the rate of intraoperative complications. To minimize baseline differences between the groups, propensity-score matching was employed in a 1:1 fashion, balancing the groups on preoperative factors including age, sex, back and leg pain, ODI, EQ-5D, and previous spine surgery. Result: The matched cohort included 211 patients in each cohort. There was no significant difference between the groups in the mean score on the ODI at two years (PLIF: 33 ± 20 vs. TLIF: 35 ± 20, P  = 0.328). We found no statistically significant differences in EQ-5D score (0.54 ± 0.35 vs. 0.51 ± 0.34, P  = 0.327), VAS score for back pain (47 ± 32 vs. 48 ± 29, P  = 0.570) or leg pain (42 ± 33 vs. 41 ± 32, P  = 0.936) between the PLIF and TLIF groups, respectively, at 2-year follow-up. Dural tears occurred in 9.5% in the PLIF group and 1.9% in the TLIF group ( P  = 0.002) corresponding to a relative risk of 5.0 (95% CI 1.7–14.4). Conclusion: We found no significant difference in PRO at 2-year follow-up between PLIF and TLIF for the treatment of lumbar disc degeneration. PLIF is associated with a five times higher risk of dural tears. Level of Evidence: 3 Abstract : This study analyzed prospectively collected data on patient-reported outcome and intraoperative complications in patients undergoing lumbar interbody fusion. We found no difference in patient-reported outcome 2 years after surgery using either posterior- or transforaminal interbody fusion. The posterior approach was associated with five times higher odds of dural tears.